Polymeric Membranes of Chitosan/Aloe Vera Gel Fabrication With Enhanced Swelling and Antimicrobial Properties for Biomedical Applications - Dure N. Iqbal; Atira Munir; Mazhar Abbas; Arif Nazir; Zahid Ali; Samar Z. Alshawwa; Munawar Iqbal; Naveed Ahmad (SAGE Publishing, 2023)
Since ancient times, medicinal plants have been used as traditional medicine to treat a variety of ailments. Aloe vera (AV) gel's therapeutic potential is one of the most effective approach in the fabrication of functional materials. The current study aimed to prepare the AV and chitosan (CS) membranes using various cross-linkers that were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform-infrared (FT-IR) spectroscopy, thermal gravimetric analysis (TGA), and ultraviolet-visible (UV-Visible) techniques, as well as swelling ratio and antimicrobial studies. SEM analysis revealed that the membrane is porous, with interconnected pores. The inclusion of AV contents in the membrane improved thermal stability and crystallinity. The swelling ratio of the ACPG-3 membrane with a 2:1 CS to AV ratio was 366%. The membranes showed promising antimicrobial activity against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Pasteurella multocida strains. The findings revealed that polymeric CS/AV membranes have effective potential for use in the biomedical field.